ENERGY SECURITY OF THE STATE: COMPARATIVE ANALYSIS AND IMPROVING THE REGULATORY FRAMEWORKS FOR ENERGY, RESOURCE EFFICIENCY OF BUILDINGS IN UKRAINE AND IN THE EU (Economics and region, 2017)
UDK 658.264GEL: E21; F15; L74; Q49; Q48; R58Victor Chichulin, Ph.D., Assoc. Prof. Kseniya Chichulina, Ph.D. Poltava National Technical Yurii Kondratyuk University. Energy Security of the state: Comparative analysis and Improving the Regulatory frameworks for energy, resource efficiency of buildings in Ukraine and in the EU. The article was the analysis and compare existing regulatory frameworks for energy and resource efficiency of various buildings in Ukraine and in the EU. The main assignment of the present research is studying the current situation and trends towards improvement of the Ukrainian regulatory framework concerning energy saving in the construction engineering sector. With the aim of ensuring energy security of the state determined approaches to effectively addressing the problem of high energy consumption. Efficient solution of the high energy resources consumption problem in the field of industrial and civil engineering is only possible with an integrated approach. It is necessary both to control heat losses by means of walling and to reduce energy consumption for conditioning buildings, ventilation air transporting, etc. To successfully solve the problem of high energy resources consumption, it is necessary to improve the total costs of producing electricity, heat/cold, to minimize losses on their way from the energy manufacturer to the consumer. The article presents: energy classification houses by European standards, proved the need to develop the existing regulations energy efficiency in Ukraine; the experience of European countries for energy certification in order to introduce in Ukraine; the structure of the legislative framework of Ukraine in the sphere of energy efficiency of buildings; implementing European practices energy conservation in Ukraine; development of recommendations on adaptation of Ukraine standards to EU; the formation of proposals for  deepening energy cooperation between Ukraine and the EU.Keywords: energy security, regulatory framework, energy and resource efficiency, buildings, energy performance certificates.